Uranyl Binding to Proteins and Structural-Functional Impacts - Lin, Ying-Wu (Biomolecules (Basel, Switzerland), 2020)
The widespread use of uranium for civilian purposes causes a worldwide concern of its threat to human health due to the long-lived radioactivity of uranium and the high toxicity of uranyl ion (UO22+). Although uranyl–protein/DNA interactions have been known for decades, fewer advances are made in understanding their structural-functional impacts. Instead of focusing only on the structural information, this article aims to review the recent advances in understanding the binding of uranyl to proteins in either potential, native, or artificial metal-binding sites, and the structural-functional impacts of uranyl–protein interactions, such as inducing conformational changes and disrupting protein-protein/DNA/ligand interactions. Photo-induced protein/DNA cleavages, as well as other impacts, are also highlighted. These advances shed light on the structure-function relationship of proteins, especially for metalloproteins, as impacted by uranyl–protein interactions. It is desired to seek approaches for biological remediation of uranyl ions, and ultimately make a full use of the double-edged sword of uranium.